In vitro assessment of the nutritive value of mixtures of leaves from tropical fodder trees - Rosales M., M; Rosales M., Mauricio (1996)
﻿ Previous work in animal nutrition has focused on single feeds and assumed additivity in ration systems. In the tropics, farmers are likely to feed mixtures of feeds, including tree fodders, which may not be simply additive in nutritional terms. This study has increased our understanding of the mechanisms that determine the associative effects on the in vitro fermentation of mixtures of fodder tree leaves. Associative effects are governed by a synchronisation in the fermentation rates of the components of the mixture. This is in turn dependent on the fermentability of their chemical constituents. Effects were demonstrated by changes in the fermentation kinetics of gas production curves. The chemical components of fodder tree leaves that affect the fermentation, and the time at which the effect occurs, were identified, using two media of different nitrogen contents. The fermentation of mixtures of pure chemical entities in various combinations was then examined. The greatest associative effects were found when the mixture had components of similar fermentability. It is proposed that associative effects are a function of the synchronisation of fermentation of the different components and was shown to occur at the point when the rate was maximal. With two types of protein (casein and bovine serum albumin (BSA)), utilisation of a protein by rumen microbes was shown to be a function of its fermentability and not of its solubility. This is also influenced by the type of associated carbohydrate. Fodder tree leaves were then combined with different pure chemical entities. Associative effects between fodder tree leaves and carbohydrates were shown to occur and the responses were similar to those obtained with mixtures of pure carbohydrates and proteins. The effect of tannins and phenolic compounds was studied using quebracho tannin as a model, and in five of the tree species. They were shown to affect the fermentability of both carbohydrates and proteins. The effect was greater with carbohydrates of medium to low fermentability. They also reacted with both soluble and insoluble protein. Forages with phenolic compounds showed both positive and negative effects. The effects were possible due to a synchrony or asynchrony in the release of protein. In mixtures of leaves from different species, associative effects were related to their fermentability. Again, this appeared to be the result of the synchronisation of the release of nutrients. Associative effects with fodder tree leaves were of a composite nature and can be both positive and negative. The implications of these findings in relation to in vivo digestion and animal production are discussed. Due to the diversity of fodder trees, there is the potential to develop feeding systems based on mixtures which make better use of available resources. This will also contribute to improved efficiency in the management and use of natural resources, and take advantage of natural plant diversity in the tropics.